The completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey: measurement of the growth rate of structure from the small-scale clustering of the luminous red galaxy sample. Issue 1 (25th July 2022) - Chapman, Michael J; Mohammad, Faizan G; Zhai, Zhongxu; Percival, Will J; Tinker, Jeremy L; Bautista, Julian E; Brownstein, Joel R; Burtin, Etienne; Dawson, Kyle S; Gil-Marín, Héctor; de la Macorra, Axel; Ross, Ashley J; et al.
ABSTRACT: We measure the small-scale clustering of the Data Release 16 extended Baryon Oscillation Spectroscopic Survey Luminous Red Galaxy sample, corrected for fibre-collisions using Pairwise Inverse Probability weights, which give unbiased clustering measurements on all scales. We fit to the monopole and quadrupole moments and to the projected correlation function over the separation range 7-60 h^-1Mpc with a model based on the aemulus cosmological emulator to measure the growth rate of cosmic structure, parametrized by fσ 8 . We obtain a measurement of fσ 8 ( z = 0.737) = 0.408 ± 0.038, which is 1.4 σ lower than the value expected from 2018 Planck data for a flat ΛCDM model, and is more consistent with recent weak-lensing measurements. The level of precision achieved is 1.7 times better than more standard measurements made using only the large-scale modes of the same sample. We also fit to the data using the full range of scales 0.1–60 h^-1Mpc modelled by the aemulus cosmological emulator and find a 4.5 σ tension in the amplitude of the halo velocity field with the Planck + ΛCDM model, driven by a mismatch on the non-linear scales. This may not be cosmological in origin, and could be due to a breakdown in the Halo Occupation Distribution model used in the emulator. Finally, we perform a robust analysis of possible sources of systematics, including the effects of redshift uncertainty and incompleteness due to target selection that were not included in previous analyses fitting to clustering measurements on small scales.